PERBUATAN PIDANA DAN PERTANGGUNGJAWABAN PIDANA DALAM PERKARA KORUPSI ANGELINA PATRICIA PINGKAN SONDAKH (Studi Putusan Mahkamah Agung Nomor 1616 K/Pid.SUS/2013) - Ibrahim Ali; Syafruddin Kalo; Mahmud Mulyadi; Suhaidi Suhaidi (Universitas Quality, 2020)
Differences among judges stem from the understanding adhered to in criminal enforcement and criminal responsibility. Fulfillment of criminal acts of corruption committed by convicts to lead project budgets at the Ministry of National Education and the Ministry of Youth and Sports to the Permai Group. The problem is the criminal responsibility in the Supreme Court Decision Number 1616 K / Pid.Sus / 2013, causing differences of opinion between court judges. Not the criminal act of corruption committed by convicted persons related to shifting the budget at the Ministry of National Education and the Ministry of Youth and Sports to the Permai Group to take care of the formulation of the elements in Article 12 letter a of the UUPTPK. Subjective elements include state administrators, reasonably presumed, while the objective includes receiving gifts or promises, and the objective of moving the project budget to Permai Group, contrary to its obligations. The results of the study show that criminal liability in this case fulfills the unintentional act of bribery, not active gratification, because there is an agreement between the bribe giver and the bribe recipient. Judges of the Central Jakarta District Court and PT DKI Jakarta must interpret the law and facts better and carefully with an understanding of dualism in criminal conviction, and should also say that the formulation of Article 12 letter a of the UUPTPK contains the offense of bribery, not active gratification.